2018
DOI: 10.2147/ijn.s173216
|View full text |Cite
|
Sign up to set email alerts
|

Design of a transdermal formulation containing raloxifene nanoparticles for osteoporosis treatment

Abstract: PurposeIn the clinical setting, raloxifene, a second-generation selective estrogen receptor modulator, is administered orally; however, the bioavailability (BA) is only 2% because of its poor solubility in aqueous fluids and its extensive first-pass metabolism. Therefore, it is expected that the development of a transdermally delivered formulation may reduce the necessary dose without compromising its therapeutic efficacy. In this study, we designed transdermal formulations containing raloxifene nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 39 publications
2
75
0
Order By: Relevance
“…We have also reported the method for preparing solid nanoparticles using bead mill treatment and showed that the addition of HPβCD and MC enhances the dispersion stability and crushing force, respectively [15,[17][18][19]. In addition, our previous studies using indomethacin showed a hydrophilic gel base, such as carbopol, provides for a high drug release of solid nanoparticles from the gel [15,[17][18][19]. Based on these findings, HPβCD, MC and carbopol were selected as components of TL-NPs-Gel in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have also reported the method for preparing solid nanoparticles using bead mill treatment and showed that the addition of HPβCD and MC enhances the dispersion stability and crushing force, respectively [15,[17][18][19]. In addition, our previous studies using indomethacin showed a hydrophilic gel base, such as carbopol, provides for a high drug release of solid nanoparticles from the gel [15,[17][18][19]. Based on these findings, HPβCD, MC and carbopol were selected as components of TL-NPs-Gel in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Type SM-4 methylcellulose (MC) and 2-hydroxypropyl-β-cyclodextrin (HPβCD) were provided by Shin-Etsu Chemical Co., Ltd. (Tokyo, Japan) and Nihon Shokuhin Kako Co., Ltd. (Tokyo, Japan), respectively. The HPβCD and MC were selected to enhance the dispersion stability and crushing force, respectively [15,[17][18][19]. Mixtures of these reagents (TL powder, MC and HPβCD) were dispersed in distilled water, and zirconia beads (0.1 mm in diameter) were added.…”
Section: Preparation Of Ophthalmic Formulations Containing Tlmentioning
confidence: 99%
See 2 more Smart Citations
“…The strategic mechanism for terpene penetration occurs through interaction with SC intercellular lipids [57]. Terpenes are applied alone or in combination with other drug delivery systems as permeation enhancers for therapeutic applications [58][59][60][61]. But beside the potency of terpenes in comparison to different penetration enhancers, the toxicities of terpenes should be considered.…”
Section: Potency Versus Toxicity Of Terpenes As One Of the Main Compomentioning
confidence: 99%